ANALYSIS OF FACTORS AFFECTING THE PURCHASE DECISION - Muammar Sajali; Satria Tirtayasa (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to determine the effect of the Store Atmosphere on purchasing decisions, to determine the effect of location on purchasing decisions, to determine the effect of Wi-fi on purchasing decisions, to determine the effect of product quality on purchasing decisions, to determine the effect of product quality on purchasing decisions. determine the effect of price on purchasing decisions at coffee shops in the city of Medan. The population in this study are consumers who make purchases at coffee shops in Medan City, where the sample in this study is 180 consumers. The data collection technique used in this study was a questionnaire. The analytical technique used in this research is SM-PLS. The conclusion of this study proves that the Store Atmosphere has a positive and significant influence on Purchase Decisions at coffee shops in Medan City, Location (Location) has a negative and insignificant effect on Purchase Decisions at coffee shops in Medan City, Internet Service/Wi-fi has a positive and significant influence on purchasing decisions at a coffee shop in the city of Medan, product quality has a positive and significant effect on purchasing decisions at a coffee shop in the city of Medan, price has a negative and insignificant effect on purchasing decisions at a coffee shop in the city of Medan.